A Modern Dilemma: How Experts Grapple with Ambiguous Genetic Test Results. (July 2020) - Scherr, Courtney L.; Ross Arguedas, Amy A.; Getachew-Smith, Hannah; Marshall-Fricker, Charlotte; Shrestha, Neeha; Brooks, Kayla; Fischhoff, Baruch; Vadaparampil, Susan T.
Objective . Clinicians regularly use panel genetic testing to identify hereditary breast cancer risk, but this practice increases the rate of receiving an ambiguous test result, the variant of uncertain significance (VUS). VUS results are a growing and long-term challenge for providers and have caused negative patient outcomes. The objective of this study was to elicit expert opinions about patients' decision making after receiving a VUS result to provide future guidance for VUS disclosure.Methods . Using an adapted mental models approach, experts ( N = 25) completed an online survey and in-depth interview eliciting qualitative judgments of the factors relevant to informed patient decision making after receiving a VUS result. Content analysis of interview transcripts clarified the basis for these judgments.Results . Participants identified 11 decisions facing patients after receiving VUS results grouped into ambiguity management or risk management. The experts also identified 24 factors relevant to each decision, which reflected 2 themes: objective factors (e.g., clinical information, guidelines) and psychosocial factors (e.g., understanding or risk perception).Conclusion . This study presents an adaptation of the mental models approach for communication under conditions of ambiguity. Findings suggest providers who present VUS results from genetic testing for hereditary breast cancer should discuss decisions related to ambiguity management that focus on hope for future reclassification, and be directive when discussing risk management decisions. Objective and psychosocial factors should influence both ambiguity and risk management decisions, but especially risk management decisions.